First outbreak of colonization by linezolid- and glycopeptide-resistant Enterococcus faecium harbouring the cfr gene in a UK nephrology unit. Issue 4 (December 2017) - Inkster, T.; Coia, J.; Meunier, D.; Doumith, M.; Martin, K.; Pike, R.; Imrie, L.; Kane, H.; Hay, M.; Wiuff, C.; Wilson, J.; Deighan, C.; et al.
Summary: Aim: To describe an outbreak of colonization by linezolid- and glycopeptide-resistant Enterococcus faecium harbouring the cfr gene in a UK nephrology unit. Methods: Isolates of linezolid-resistant E. faecium were typed by pulsed-field gel electrophoresis (PFGE), and examined by polymerase chain reaction (PCR) and sequencing for the transmissible cfr gene that confers resistance to linezolid. Enhanced environmental cleaning, initial and weekly screening of all patients, and monitoring of adherence to standard infection control precautions were implemented. Findings: Five patients with pre-existing renal disease were found to have rectal colonization with linezolid-resistant E. faecium over a two-week period. The index case was a 57-year-old male from India who had travelled to the UK. One patient also had a linezolid-resistant E. faecium of a different PFGE profile isolated from a heel wound. All isolates were confirmed to harbour the cfr gene by PCR and Sanger sequencing, and all were resistant to glycopeptides (VanA phenotype). Conclusions: This article describes the first UK outbreak with a single strain of linezolid- and glycopeptide-resistant E. faecium harbouring the cfr gene, affecting five patients in a nephrology unit. Following the implementation of aggressive infection control measures, no further cases were detected beyond a two-week period.